Metode Analitical Hierarchy Process (AHP) Dalam Pemilihan Umum Presiden Indonesia 2019 - Evan Rosiska; Rika Harman (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2019)
Election is an activity carried out by a community in selecting people who occupy certain political positions. Before making an election, socialization is carried out by people who will take up the political position. The tendency of the community when making elections in determining which candidates will be chosen, the community does not assess the overall potential possessed by each candidate, even the community only sees one of the potential possessed by the candidate, from the results of a temporary survey conducted by asking questions directly to 10 respondents in the field, 4 respondents determined their choice based on popularity only, 3 respondents looked in terms of organization and the way of campaign of each candidate, the rest there were those who made choices when they were selected. so we need a system that supports making a decision, the application of the Analitycal Hierarchy Proccess (AHP) method as an reinforcer and supports in making a decision based on characteristics that are considered to represent the whole. The data used in the form of quantitative data from weighting is done through distributing questionnaires to the sample. From the analysis process carried out to help make a decision in the 2019 Presidential election, it can be concluded that the most important priorities to the last are Competence (46.82%), Aspectivity (25.50%), Integrity (13.54%), Electability (7.19%), Campaign (4.51%) Coalition Party (2.42%). Whereas for alternative use data is obtained, namely the highest value weight, namely candidate pairs with Number. Sort 01 (Joko Widodo and Ma'ruf Amin) with a score of 85.9%. while the candidate pairs with serial number 02, Prabowo Subianto and Sandiaga Uno, scored 14.1%.